Дослідження впливу добавок гідробіонтів і молочної кислоти на газоутворюючу здатність зернової суміші для хлібобулочних виробів - Крамаренко, Дмитро Павлович (НТУ "ХПІ", 2017)
Стаття присвячена дослідженню впливу добавок гідробіонтів і молочної кислоти на газоутворюючу здатність зернової суміші для хлібобулочних виробів. Як свідчать отриманні данні в якості джерел молочної кислоти при ферментації зернової суміші найбільш ефективними на процес газоутворення виявися вплив концентрату молочнокислої закваски та підсирної молочної сироватки, зразки з використанням яких мають швидкість газоутворення 11,73 см3/хв і 10,56 см3/хв відповідно. Максимуми газоутворення знаходяться в інтервалі 15-25 хвилин та 50-70 хвилин. Всі дослідні добавки гідробіонтів сприяють інтенсифікації процесу бродіння тіста і розстоювання тістових заготовок внаслідок збагачення тіста біологічно активними сполуками, що призводить до активізації і життєдіяльності дріжджових клітин. Найбільш ефективно впливає на швидкість газоутворення добавка гідролізату з молюсків, які підвищує її на 22,66-26,01% в порівнянні з контролем. Добавка цистозіри підвищує загальну швидкість газоутворення на 19,35-22,98%, а добавка ряски на 12,68-16,56%.

Baked goods are regularly massively consumed products. By regulating their chemical composition, we can significantly influence the diet and human health. In solving this problem, the promising is the production of baked goods from whole grains, which allows maximum preservation of inherent nutritional potential of grains and the use of marine dietary adjuncts, marine and fresh-water algae, fish flour, and hydrolysates in the formulation. One of the critical indicators characterizing the intensity of alcohol fermentation during the dough preparation is gassing, which greatly affects the volume and doughiness of semifinished products from the dough and the porosity of bread structure. Therefore, the objective of this article was to study the effect of sources of lactic acid and adjuncts plant and animal hydrobionts on the gassing process in grain mixture for baked goods. At the first stage of the study, a change in the amount of formed gas and the rate of gas formation in the dough in the production of grain bread were determined, depending on the sources of lactic acid. At the second stage, the effect of hydrobiont adjuncts on the process of gas formation was determined. According to the data obtained, the lactic acid starter concentrate and cheese whey as a source of lactic acid in the fermentation of the grain mixture have the most beneficial effect on the process of gas formation. A gas formation rate of the samples with these adjuncts is 11.73 cm3/min and 10.56 cm3/min, respectively. Maximums of gas formation are in the range of 15-25 minutes and 50-70 minutes. All hydrobionts adjuncts used in the studies contribute to the intensification of the fermentation test and the separation of test blanks due to the enrichment of the dough with biologically active compounds, which leads to the activation of the processes of yeast cells vital activity. Addition of hydrolysates from mollusks has the greatest effect on the rate of gas formation, increasing it by 22.66-26.01% compared to control. The addition of cystoseira increases the overall rate of gas formation by 19.35-22.98%, and the addition of duckweed - by 12.68-16.56%. The prospect of further researches is the study of the influence of hydrobionts adjuncts on physical and chemical changes in the yeast dough and flour technologies development with their use.
Research of the effect of hydrobionts and lactic acid adjuncts on the gassing power of grain mixture for baked goods
Keywords: харчування здорове; цистозіра; ряска; ферментація; baked goods; hydrobionts; grain mixture; gassing; lactic acid